2010
DOI: 10.1002/cncr.25748
|View full text |Cite
|
Sign up to set email alerts
|

Tumor flare reaction associated with lenalidomide treatment in patients with chronic lymphocytic leukemia predicts clinical response

Abstract: Age standardized incidence rates of breast cancer in developed countries is nearly threefold higher than in developing countries. Iran has had one of the lowest incidence rates for breast cancer in the world, but during the last four decades increasing incidence rates of breast cancer made it the most prevalent cancer in Iranian women. After adjustment for age, Iranian young women are at relatively higher risk of breast cancer than their counterparts in developed countries. The purpose of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 53 publications
3
49
0
Order By: Relevance
“…Furthermore, immunomodulatory drugs that seem to act to a large extent by down-regulating prosurvival factors such as VEGF, TNF, IL-8, and IL6, 46,48 may act in part by altering cytokine CL composition or relationships. The finding that tumor flare reaction that can occur with lenalidomide treatment predicts clinical response in CLL 49 suggests that modulation of inflammation contributes to the effectiveness of this drug; this is consistent with our finding that CLs of proinflammatory cytokines correlate with better outcome (CL2 and CL3).…”
supporting
confidence: 91%
“…Furthermore, immunomodulatory drugs that seem to act to a large extent by down-regulating prosurvival factors such as VEGF, TNF, IL-8, and IL6, 46,48 may act in part by altering cytokine CL composition or relationships. The finding that tumor flare reaction that can occur with lenalidomide treatment predicts clinical response in CLL 49 suggests that modulation of inflammation contributes to the effectiveness of this drug; this is consistent with our finding that CLs of proinflammatory cytokines correlate with better outcome (CL2 and CL3).…”
supporting
confidence: 91%
“…78 Although inhibition of inflammatory cytokine secretion might improve its tolerability, the combination could also decrease the clinical benefit of lenalidomide, given evidence that its efficacy in CLL depends on the activation of an adaptive immune response. 79,80 The clinical success of such combinations may therefore depend on a more detailed understanding of differences between the various BCR inhibitors in regards to what pathways are inhibited and the resulting impact on cellular networks.…”
Section: Redefining Treatment Goals and The Development Of Rational Cmentioning
confidence: 99%
“…Prophylaxis with low-dose oral prednisone (20 mg for 5 days followed by 10 mg for 5 days) decreased severity and delayed onset but did not reduce the incidence and may slow resolution (Chanan-Khan et al, 2011). Tumor flare reaction has also been reported mainly within the first cycle of lenalidomide in relapsed MCL patients, including 13/134 patients (10%, all grade 1/2) in the MCL-001 study and 4/26 patients (15%; 3 grade 2) reported by Eve and Rule (Eve & Rule, 2010;Goy et al, 2013).…”
Section: Tumor Flare Reactionmentioning
confidence: 94%